Reducing Inflammation and Vascular Invasion in Intervertebral Disc Degeneration via Cystathionine-γ-Lyase Inhibitory Effect on E-Selectin - Xu, Haoran; Wei, Kang; Tu, Jingyao; Chen, Yangmengfan; He, Yi; Ding, Yifan; Xu, Huanhuan; Bao, Xinyu; Xie, Hui; Fang, Huang; Wang, Huan (Frontiers in Cell and Developmental Biology, 2021)
The incidence of degenerative spinal diseases, such as cervical spondylosis and thoracic and lumbar disc herniation, is increasing. These health problems have adversely affected human life and work. Surgical intervention is effective when intervertebral disc degeneration (IDD) causes nerve compression and/or severely limits daily activity. Early IDD patients generally do not require surgery. However, there is no effective method of impeding IDD progression. Thus, novel approaches of alleviating IDD deterioration are urgently required. Cystathionine-γ-lyase (CSE) and E-selectin (CD62E) are vital factors regulating vascular function and inflammation. However, their effects on IDD and vascular invasion in intervertebral discs (IVD) are pending further exploration. Here, bioinformatics and human nucleus pulposus (NP) tissues analyses revealed that CSE was significantly downregulated and CD62E was upregulated in the NP tissues of IDD patients. We demonstrated that CSE overexpression, CD62E downregulation, and NF-κB (P65) inhibition mitigate inflammation and recover metabolic function in NP cells. Similarly, CSE attenuated vascular invasion induced by inflammatory irritation. Using a rat IDD model, we showed that CSE improved degeneration, inflammation, and microvascular invasion in NP tissue, whereas CD62E had the opposite effect. Taken together, our results indicated that the CSE/CD62E pathway could effectively improve the inflammatory environment and vascular invasion in IVD. Hence, the findings of this study propose a promising and valuable strategy for the treatment of patients with early IDD as well as postoperative adjuvant therapy in patients with severe IDD.